1998
DOI: 10.1042/bj3340057
|View full text |Cite
|
Sign up to set email alerts
|

Thioltransferase activity of bovine lens glutathione S-transferase

Abstract: A Mu-class glutathione S-transferase purified to electrophoretic homogeneity from bovine lens displayed thioltransferase activity, catalysing the transthiolation reaction between GSH and hydroxyethyldisulphide. The thiol-transfer reaction is composed of two steps, the formation of GSSG occurring through the generation of an intermediate mixed disulphide between GSH and the target disulphide. Unlike glutaredoxin, which is only able to catalyse the second step of the transthiolation process, glutathioneS-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“…Similarities in the protein fold of the glutaredoxins and the N-terminal domain of the cytosolic GSTs have been noted (34), and low thiol transferase activity (74.3 nmol/mg/min) has been attributed to a Mu class GST from bovine lens (35). In other unpublished studies we examined the thiol transferase activity of a range of GSTs from the Alpha, Mu, Pi, Theta, and Zeta classes (GSTA 1-1, GST 2-2, GSTA 4-4, GSTM 1-1, GSTM 2-2, GSTM 3-3, GSTM 4-4, GSTP 1-1, GSTT 2-2, GSTT 1-1, GST Z 1-1).…”
Section: Dna and Proteinmentioning
confidence: 99%
“…Similarities in the protein fold of the glutaredoxins and the N-terminal domain of the cytosolic GSTs have been noted (34), and low thiol transferase activity (74.3 nmol/mg/min) has been attributed to a Mu class GST from bovine lens (35). In other unpublished studies we examined the thiol transferase activity of a range of GSTs from the Alpha, Mu, Pi, Theta, and Zeta classes (GSTA 1-1, GST 2-2, GSTA 4-4, GSTM 1-1, GSTM 2-2, GSTM 3-3, GSTM 4-4, GSTP 1-1, GSTT 2-2, GSTT 1-1, GST Z 1-1).…”
Section: Dna and Proteinmentioning
confidence: 99%
“…The authors noted that no S-glutathionylated protein was formed in these null mice and using isolated protein, they elegantly demonstrated that sulfenic acid formation on aldose reductase was required before GST could transfer GSH to the protein leading to the formation of a mixed disulfide (162,171). These data suggest that GST or other similar proteins can be used as a carrier of GSH and act as an intermediate in the Sglutathionylation process of target proteins (42). Furthermore, GSTs might also provide localized redox signaling.…”
mentioning
confidence: 95%
“…50,51) Furthermore, GSTM exhibits a dethiolate activity such as that of thioltransferase, suggesting that GSTM plays an important role in the cleavage of the mixed disulfides produced under oxidative stress. 19,26) These results suggest that GSTs play a role as an important anti-oxidant enzyme under oxidative stress. Indeed, epidemiological studies have been presented the implication of GST M1 having an important role in cataractogenesis.…”
Section: Resultsmentioning
confidence: 75%
“…The thioltransferase-like (TTase-like) activity is the most characteristic property of GSTM. 19) The first report of this activity was presented in a paper on bovine lens GSTM by Raghavachari, N. et al 26) TTase, a small enzyme of < 10 kDa, can catalyze the thiol/ disulfide exchange reaction between small molecular weight thiols and proteins, and plays an important role in the redox regulation of protein thiols in living cells. [27][28][29][30] We have previously reported that TTase displays a strong sensitivity against oxidants, including disulfides.…”
Section: -Class Glutathione S-transferasementioning
confidence: 99%
See 1 more Smart Citation